Vacuole–mitochondrial cross-talk during apoptosis in yeast: a model for understanding lysosome–mitochondria-mediated apoptosis in mammals. (21st September 2011) - Sousa, Maria João; Azevedo, Flávìa; Pedras, Ana; Marques, Carolina; Coutinho, Olga P.; Preto, Ana; Gerós, Hernâni; Chaves, Susana R.; Côrte-Real, Manuela
Abstract : The yeast apoptosis field emerged with the finding that key components of the apoptotic machinery are conserved in these simple eukaryotes. Thus it became possible to exploit these genetically tractable organisms to improve our understanding of the intricate mechanisms of cell death in higher eukaryotes and of severe human diseases associated with apoptosis dysfunctions. Early on, it was recognized that a mitochondria-mediated apoptotic pathway showing similarities to the mammalian intrinsic pathway was conserved in yeast. Recently, lysosomes have also emerged as central players in mammalian apoptosis. Following LMP (lysosomal membrane permeabilization), lysosomal proteases such as cathepsins B, D and L are released into the cytosol and can trigger a mitochondrial apoptotic cascade. CatD (cathepsin D) can also have anti-apoptotic effects in some cellular types and specific contexts. Nonetheless, the mechanisms underlying LMP and the specific role of cathepsins after their release into the cytosol remain poorly understood. We have recently shown that yeast vacuoles, membrane-bound acidic organelles, which share many similarities to plant vacuoles and mammalian lysosomes, are also involved in the regulation of apoptosis and that the vacuolar protease Pep4p, orthologue of the human CatD, is released from the vacuole into the cytosol in response to acetic acid. Here, we discuss how the conservation of cell-death regulation mechanisms in yeast by the lysosome-like organelle and mitochondria may provide new insights into the understanding of the complex interplay between the mitochondria and lysosome-mediated signalling routes during mammalian apoptosis.